The New Digital Economy and Sustainability: Challenges and Opportunities - Rosário, Albérico Travassos; Dias, Joana Carmo (Sustainability, 2023)
This study aims to analyze the interconnection between the concepts of digital economy and sustainability. These concepts have become popular due to awareness of climate change and the increased development and adoption of technologies. Researchers, business leaders and policymakers are exploring the many ways digital technologies can be used to address sustainability issues. Using a systematic literature review with a bibliometric analysis, we examined a sample of 92 studies indexed in SCOPUS to identify research activity on this topic up until April 2023. We found that 2022 had the highest number of peer-reviewed articles, with 31 publications. During the research, we identified multiple opportunities for this interconnection, such as developing renewable energies and sustainable technological solutions, smart cities and sustainable urbanization, and sustainable consumption. These opportunities enabled by digital technologies allow companies to adopt sustainable business strategies and develop sustainable products. Despite these opportunities, the digital economy presents several challenges that can hinder efforts to achieve sustainability goals, such as increasing e-waste, high energy consumption and rising carbon emissions, the digital divide, job insecurity, growing monopolies, and data protection. These issues must be addressed to enable the optimal use of the opportunities presented in the digital economy to promote sustainability.